1996
DOI: 10.1007/bf01803781
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the development of recombinant vaccines for the immunotherapy of breast cancer

Abstract: The development of recombinant vaccines for specific immunotherapy of carcinoma represents a novel approach for the treatment of breast cancer and other tumor types. This article reviews the various parameters that should be considered in the development of recombinant vaccines. Several breast cancer associated antigens are also discussed which may provide potential target molecules. The human carcinoembryonic antigen (CEA), which is expressed on approximately 50% of breast cancers, represents one such target … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2001
2001
2006
2006

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…42,44,46,57 -59 In some of those studies, costimulatory molecules or cytokines were used to enhance vaccine effects. 44,45,59,64 These studies have suggested a role for antibodies, 36 -41,43,47,48,51 -53,60,63,64 CTL, 36 -48 and delayed-type hypersensitive T cells, 36,37,46,53 although the role of these factors was not directly demonstrated by in vivo cell depletion or adoptive cell transfer. The mouse models targeting human carcinoembryonic Ag (CEA ) and MUC-1 with VV vaccines, 36,39 -41,43,45 -48,52,63 similar to the human GA733 model used in the present study, include Ags that are expressed by tumors and by normal tissues.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…42,44,46,57 -59 In some of those studies, costimulatory molecules or cytokines were used to enhance vaccine effects. 44,45,59,64 These studies have suggested a role for antibodies, 36 -41,43,47,48,51 -53,60,63,64 CTL, 36 -48 and delayed-type hypersensitive T cells, 36,37,46,53 although the role of these factors was not directly demonstrated by in vivo cell depletion or adoptive cell transfer. The mouse models targeting human carcinoembryonic Ag (CEA ) and MUC-1 with VV vaccines, 36,39 -41,43,45 -48,52,63 similar to the human GA733 model used in the present study, include Ags that are expressed by tumors and by normal tissues.…”
Section: Cancer Gene Therapymentioning
confidence: 99%
“…CEA expression is prevalent among diverse human carcinomas, namely, colorectal, gastric, pancreatic, breast, and nonsmall cell lung malignancies (10). Transgenic mice expressing the human CEA gene as "self" in tissues similar to expression in humans were used as a more relevant preclinical model to investigate various experimental immunotherapies (11).…”
Section: Introductionmentioning
confidence: 99%
“…Despite these considerations, our results can be relevant for vaccination in humans. For instance, recent research with vaccinia virus recombinants in people demonstrated that in humans, as in mice, preexisting immunity to vaccinia virus limits the effectiveness of recombinant vaccinia virus vectors (7,24). Therefore, at least in the case of vaccinia virus, results in mice predict the outcome in humans.…”
Section: Discussionmentioning
confidence: 99%